Examining pre-service teachers' professional identity ahead of teaching practicum - Ika Wahyuni Lestari; Rudi Hartono; Januarius Mujiyanto; Zulfa Sakhiyya (Issues in educational research, 2024)
There has been extensive research on pre-service teachers' professional identity; however, there remains a gap on its examination prior to teaching practicum engagement. Considering its significance in succeeding and providing meaningful actual teaching experiences through a practicum program, the present study aimed to address the gap by examining the professional identity of pre-service teachers before they engaged in teaching practicum. Under a mixed methods design, data were collected using a questionnaire distributed to ninety third-year pre-service EFL teachers (PSETs) in Indonesia (Nequivalent90), nine of whom (nequivalent9) were interviewed. The results showed a moderate level of professional identity shaped ahead of practicum. It suggested a developing process of professional identity construction among pre-service teachers and needs for improvement, particularly regarding their self-efficacy in teaching, their commitment to teaching, and their perceptions toward the teaching profession. Positively, the pre-service teachers demonstrated strong values of teacher professional orientation and good understanding of teachers' roles. Implications were discussed, emphasising the steps English language teacher education programs should take to strengthen PSETs' professional identity.